Anglo-American Approaches to Alliance Security, 1955-60 - Rees, W. author. aut Link
XIV, 214 p.
Keywords: This book looks at the attitudes and policies of the United States and United Kingdom, in the late 1950s, towards the three major alliances in Europe, the Middle East and South East Asia. Drawing upon a wealth of archival material, it analyses both the military relationship between the US and UK and the extent to which these two countries were prepared to cooperate with their allies in countering the threats to Western security.